Fifteen-year trends in self-reported racism and link with health and well-being of African Canadian adolescents: a secondary data analysis - Helen U. Okoye; Elizabeth Saewyc (BMC, 2021)
Abstract Background We assessed the prevalence and trends in racial discrimination among African Canadian adolescents in British Columbia. The association between racial discrimination and self-rated health, access to mental health services, substance use, suicidal thoughts and attempts, experience of extreme stress, among others were examined within the 2018 dataset. Methods Secondary analysis used the data collected from African Canadian adolescents (n = 2448) as part of the British Columbia Adolescent Health Surveys (2003-2018). We examined whether racial discrimination increased, decreased, or remained stable over time. We evaluated experiences of racial discrimination for all adolescents, and then disaggregated analyses for boys, girls, immigrant, and Canadian-born African adolescents. We used Rao-Scott's adjusted chi-square to test differences in racial discrimination and adjusted logistic regressions to test trends across survey years, widening or narrowing gaps in racial discrimination, as well as the link to health outcomes. Results Racial discrimination was significantly different across the survey years (Adjusted F = 4.60, p < .01), with the highest percentage of adolescents reporting past year racial discrimination in 2018 (29.9%) and the lowest percentage in 2013 (21.3%). Girls and immigrant African Canadian adolescents were more likely to have experienced racial discrimination. However, girls and Canadian-born adolescents had the highest odds of reporting racial discrimination in 2018 compared to 2003, AOR = 1.85, and 1.58, respectively. The findings reveal significant differences in the experiences of racial discrimination for boys and girls, as well as for immigrant and Canadian-born African adolescents. Significant differences were noted in the link between racial discrimination and self-rated health and engaging in behaviours that might expose them to health risks. The worst negative health outcomes were found for boys and immigrant African Canadian adolescents. Conclusion The study suggests that more than 1 in 4 African Canadian adolescents in British Columbia report racial discrimination, which is an increasing trend in recent years. Those who reported racial discrimination also had the worst adverse health outcomes. There is a need for more public health action to reduce racism, create awareness about the negative health impacts, and provide better support for African Canadian adolescents.